Friend Turned Foe: Bacteremia Following a Scratch by an Adopted Pekin Duck - Lefika Bathobakae MD, MPH; Hannah Cho PharmD; Simi Philip MD; Jin S. Suh MD, FACP, FIDSA (Journal of Investigative Medicine High Impact Case Reports)
Pasteurella multocida is a gram-negative coccobacillus that colonizes the aerodigestive tracts of cats, dogs, birds, and wild animals. This veterinary pathogen spreads to humans via licking, biting, or scratching. Pekin ducks are known carriers of multiple strains of Pasteurella bacteria that can manifest as fowl cholera, eye infection, or duck septicemia. This bacterium is a farmer’s nightmare, as it is associated with high mortality rates. Herein, we report a unique case of P. multocida bacteremia in an immunocompetent host that shared a house with adopted Pekin ducks.